Impact of Reforestation After Forest Fire on Infiltration and Other Soil Physical Properties - Iva Dewi Lestariningsih; Filza Roholesi Mewar; Akmaludin Dimas Anggara; Sarifudin Lathif; Ghozian Putra Sukbara; Sativandi Riza; Kurniawan Sigit Wicaksono; Yumin Wang (JOURNAL OF TROPICAL SOILS, 2024)
Forest fires have become a vital issue causing various hydro-meteorological disasters. Many parties have carried out efforts. This study aimed to analyze the impact of land covers due to reforestation on infiltration rate and other soil physical properties related to hydrological conditions. The research was conducted in the Cempaka Forest area. There are four observed land covers, i.e., Timber Forest Products (TFP), Non-Timber Forest Products (NTFP), Pine, and Shrub. The results showed that land cover significantly affected the infiltration rate (p <0.05). The infiltration rate of Pine was not significantly different from NTFP but significantly different from TFP and Shrubs. The infiltration rate of Pine, NTFP, TFP, and Shrub land cover was 76.2 cm hr-1, 48.1 cm hr-1, 32.7 cm.hr-1, and 40.0 cm hr-1, respectively. The infiltration correlated with soil bulk density at two depths (0-15 cm and 16-30 cm) with r values of 0.614 and 0.595, respectively. Infiltration rate also significantly correlated with water content at pF 0 and pF 2.5 in the second soil depth. Additionally, soil bulk density is correlated with soil particle density with r  = 0.621. Soil particle density also correlated with clay content with r equal to 0.726.